Mobile Application Prototype: AP3S to Prevent Stunted Babies - Rianti, Emy; Pujiastuti, Rr. Sri Endang; Triwinarto, Agus (International Journal of Online and Biomedical Engineering (iJOE), 2025)
Stunting in toddlers is a serious concern because it can have various short and long-term adverse effects. Therefore, it is necessary to design a mobile-based system to monitor the health of pregnant women early on so that stunted babies can be prevented. This study aims to develop a prototype of an application for early detection of stunting risk in Androidbased antenatal care services. This application prototype is made in Indonesian and is called: “Aplikasi Pendampingan Percepatan Penurunan Stunting (AP3S)”/Stunting Reduction Acceleration Assistance Application. The methodology applied is the system development life cycle (SDLC), one of the primary methods for developing mobile applications in the health sector. As a result, a prototype application with a design and functionality that facilitates access for pregnant women can connect directly with health workers and monitor and consult further. As for health workers, AP3S can provide a comprehensive health analysis of antenatal care, including nutrition for pregnant women, fetal growth monitoring, and health education. AP3S has the advantage of being able to immediately display the risk of babies born stunted or babies with low birth weight so that preventive interventions can be carried out immediately. In conclusion, after conducting a literature study and prototype development, an efficient, easy-to-use, and safe application prototype was obtained to facilitate patient access to health services to prevent babies born with stunting.